Nitrogen fertilizer improves Salix matsudana growth and soil qualities - Wang, Qian; Niu, Xiaoyun; Huang, Shuo; Di, Dongliu; Su, Beibei; Yuan, Yangchen; Wu, Yumeng; Huang, Dazhuang (Frontiers in Microbiology, 2025)
IntroductionSoil contamination with heavy metals (e.g., Pb, Cd) poses severe environmental risks due to industrialization. Salix matsudana, a metal-tolerant woody plant, shows promise for phytoremediation, yet the synergistic role of nitrogen (N) fertilization in enhancing plant growth and soil remediation remains unclear. This study aims to elucidate how N fertilization optimizes S. matsudana’s remediation efficiency.MethodsWe applied integrated physiological and multi-omics approaches to assess N fertilization effects on S. matsudana growth, Pb/Cd uptake, and rhizosphere properties. Physiological metrics (biomass, metal accumulation) were combined with microbial community analysis (16S rRNA sequencing) and metabolomic profiling (LC-MS/GC-MS) of rhizosphere soils under varying N concentrations.ResultsHigh N levels significantly increased plant biomass and Pb/Cd accumulation. Microbial diversity shifted, with enriched metal-mobilizing taxa. Metabolomics revealed elevated organic acids, correlating with improved metal bioavailability and soil health.DiscussionN fertilization synergistically enhances phytoremediation by: (1) stimulating plant growth and metal uptake, (2) reshaping rhizosphere microbiomes for metal mobilization, and (3) promoting chelating metabolite secretion. These findings provide actionable insights for optimizing N-assisted phytoremediation strategies.